Quality parameters of minced meat and raw formed products on Bosnian and Herzegovinian market - Muftić, Emina (Array, 2020)
The aim of this research was to examine physicochemical parameters of finished and semi-finished meat products: minced meat (beef, pork and mixed meat) and raw formed meat products (ćevapi, patties/burgers and sujuk sausages), and to determine quality parameters of these products on the Bosnia and Herzegovina market. Examined parameters included: protein content, fat, collagen in meat proteins and salt (NaCl). We analysed 282 samples of these products and found deviations with regard to the applicable Ordinance on minced meat and semi-finished and finished meat products of “The Law on Food of Bosnia and Herzegovina” in all parameters, except salt (NaCl). The majority of deviations referred to the content of collagen in meat proteins, with as much as 21.98 % of examined samples in violation of the applicable legislation.